Human Body Communication on Portable Biometric Authentication. Issue 1 (May 2021) - Vadivelu, R; Santhakumar, G; Kaviya, P; Menaka, M; Monisha, S; Balasubramaniam, D
Abstract: Furthermore, since people's proportions of biological tissues including muscle, fat, and skeleton vary, the total dielectric constants of the human body, as well as the signal propagated through the human body, can be used as a biometric characteristic to authenticate people using Redtacton. Wearable systems can be smaller since the HBC is used for both authentication and connectivity. HBC authentication is ideal for wearable devices independent of location due to the use of a transmission signal between devices.